TRANFORMASI AKAD PENYEWAAN TEMPAT PEMANCINGAN MADUN FISHING CLUB DI KABUPATEN KETAPANG MENJADI PERLOMBAAN BERDASARKAN KOMPILASI HUKUM EKONOMI SYARIAH BAB XI TENTANG IJARAH - Fajar Saputra Hasmidar; Moch. Riza Fahmi; Arif Wibowo (Al-Aqad, 2025)
This research was motivated by the practice of transforming contracts from renting to competitions that occurred at the Madun Fishing Club, Ketapang Regency. This research aims to find out how the Madun Fishing Club's fishing rental contract in Ketapang Regency became a competition and to find out how the Compilation of Sharia Economic Law (KHES) review transformed the object of the Madun Fishing Club's fishing rental contract in Ketapang Regency. The research approach in preparing this thesis is to use a qualitative approach with a type of empirical juridical research. Meanwhile, the secondary data in this research itself are business owners and competition participants or renters in the Madun Fishing Club. Primary data sources include journals and related documents, in this case, KHES. Data collection techniques are interviews, observation, and documentation. This data was analyzed using the theory of legal pluralism, while the technical data analysis used by researchers involved data collection, data reduction, data presentation, and drawing conclusions. Based on the data obtained, this research can conclude, namely, 1). The rental agreement for the competition held by the Madun Fishing Club in Ketapang Regency is carried out in writing individually using the Galatama competition system. In terms of implementation, this competition system as a whole uses a rental agreement. 2) The rental of the Madun Fishing Club fishing ground in Ketapang Regency, which turns into a competition, can be justified in the Compilation of Sharia Economic Law, namely in Article 29,7, which states that the ijarah contract can be changed, extended, and canceled based on agreement.